2023
DOI: 10.3389/fnagi.2023.1223310
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking, alcohol consumption, and the risk of Parkinson’s disease

Se Young Jung,
Sohyun Chun,
Eun Bin Cho
et al.

Abstract: ObjectiveThere have been no studies on the association between changes in smoking and alcohol consumption or combined changes in smoking and alcohol consumption frequencies and PD risk. To assess the influence of changes in smoking and alcohol consumption on the risk of Parkinson’s disease (PD).MethodsNational Health Insurance Service (NHIS) database between January 2009 to December 2011 was analyzed. A total of 3,931,741 patients were included. Study participants were followed up for the incidence of PD until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies evaluating the relationship between alcohol intake and PD risk have shown contrasting results [ 43 , 44 ]. However, recent studies reported that alcohol consumption at a light to moderate level is associated with a decreased risk of PD, whereas heavy drinking is not [ 45 , 46 ]. Therefore, the quantity of alcohol consumed is important for decreasing PD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluating the relationship between alcohol intake and PD risk have shown contrasting results [ 43 , 44 ]. However, recent studies reported that alcohol consumption at a light to moderate level is associated with a decreased risk of PD, whereas heavy drinking is not [ 45 , 46 ]. Therefore, the quantity of alcohol consumed is important for decreasing PD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drinking a modest amount of alcohol can be helpful and appears to have a more profound protective effect than a neurotoxic effect. SY Jung et al also reported that PD risk was reduced in non-drinkers-turned-light drinkers, and light drinkers had an increased risk of developing PD when ceasing alcohol consumption [ 45 ]. Furthermore, they also reported that smoking and alcohol consumption may have a joint protective effect against PD; however, the optimal amount may differ by race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%